Management Applied to the Traditional Pig Production System in the Colombian-Venezuelan Plains - Hernández , Milena Esney; Rodríguez, Luís Ernesto; Cardozo, Adolfo; Salamanca, Arcesio (Spei Domus, 2015)
Purpose: The purpose of this article was to analyze the traditional management applied to the production of native pigs in the Colombian-Venezuelan plains. Description: Initially, the origin of native pigs is described as an animal genetic resource that inhabits the Colombian-Venezuelan savannas, as a result of natural selection. Then, the socio-economic importance to the Venezuelan plains of Apure, Guarico and Barinas, and to the east of the Colombian departments of Casanare, Vichada, and Arauca is revealed. Some of the management practices implemented in this type of system are described and certain production indicators are shown. Point of view: Generally, the savanna pig shows particular independence from conventional production systems and, therefore, it has survived within the traditional exploitation system. This is a good example of clean production and an invitation to reflect which should be analyzed in more detail in order to adjust production to commercial parameters that allow continuity and survival of this valuable local genetic resource. Conclusions: It is concluded that there is an opportunity to offer quality organic products and that, after this reflection on the potential of savanna pig to meet the demand of sophisticated and demanding markets, it is necessary to conduct research in order to establish productive and reproductive parameters that improve the efficiency of this exploitation system with an underused pig race in the flood savanna ecosystem.